2021
DOI: 10.1155/2021/6622439
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RIPK4 Predicts Poor Prognosis and Promotes Metastasis in Ovarian Cancer

Abstract: This study was conducted to evaluate the prognostic value of receptor-interacting protein kinase 4 (RIPK4) in ovarian cancer (OC) and its role in tumorigenesis. RNA expression and the corresponding clinical data were obtained from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. The relationship between clinical-pathological characteristics and RIPK4 expression was analyzed using the Wilcoxon signed-rank test and logistic regression. The Cox regression and the Kaplan-Meier method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…RIPK4 is involved in many processes related to skin development and epidermal homeostasis, as it is required for keratinocyte differentiation. Recent studies have shown that RIPK4 plays an important role in various cancers, exhibiting both oncogenic (Gong et al 2018 ; Liu et al 2015 , 2018 , 2021 ; Qi et al 2018 ; Yi et al 2020 ) and tumor suppressive (Kopparam et al 2017 ; Li et al 2021 ; Poligone et al 2015 ; Wang et al 2014 ) functions, depending on the cellular context. In our prior study, we demonstrated heterogeneous expression of RIPK4 in melanoma samples, where it acts as an oncogene, in contrast to cutaneous squamous cell carcinoma, where it functions as a tumor suppressor (Madej et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…RIPK4 is involved in many processes related to skin development and epidermal homeostasis, as it is required for keratinocyte differentiation. Recent studies have shown that RIPK4 plays an important role in various cancers, exhibiting both oncogenic (Gong et al 2018 ; Liu et al 2015 , 2018 , 2021 ; Qi et al 2018 ; Yi et al 2020 ) and tumor suppressive (Kopparam et al 2017 ; Li et al 2021 ; Poligone et al 2015 ; Wang et al 2014 ) functions, depending on the cellular context. In our prior study, we demonstrated heterogeneous expression of RIPK4 in melanoma samples, where it acts as an oncogene, in contrast to cutaneous squamous cell carcinoma, where it functions as a tumor suppressor (Madej et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, RIPK4 expression is confirmed to be positively associated with favorable prognosis in tongue SCC, lung adenocarcinoma, and hepatocellular carcinoma ( Wang et al, 2014 ; Kopparam et al, 2017 ; Li et al, 2021 ). By contrast, RIPK4 overexpression predicts poor prognosis in patients with ovarian cancer, cervical SCC, pancreatic cancer, bladder cancer, and osteosarcoma ( Qi et al, 2018 ; Liu et al, 2015 ; Liu et al, 2018 ; Yi et al, 2020 ; Liu et al, 2021 ). We then used public data set OncoLnc ( ) ( Anaya, 2016 ) to perform survival analyses of other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, RIPK4 may have a context-specific function in different cancer progression and signal transduction ( Xu, Wei & He, 2020 ). RIPK4 expression is up-regulated and relates with a poor prognosis in ovarian cancer, cervical SCC, pancreatic cancer, bladder cancer and osteosarcoma ( Qi et al, 2018 ; Liu et al, 2015 ; Liu et al, 2018 ; Yi et al, 2020 ; Liu et al, 2021 ). However, the expression of RIPK4 is down-regulated and positively correlates with favorable prognosis in tongue SCC, hepatocellular carcinoma (HCC) and lung adenocarcinoma ( Wang et al, 2014 ; Kopparam et al, 2017 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few of reports regarding the role of RIPK4 and potential mechanism in OC. Liu et al have reported that RIPK4 can act as a potential prognostic molecular marker for poor survival and promoted tumor metastasis in OC (S. Liu et al, 2021). In addition, another study also showed that miR‐330‐3p suppressed the progression of OC by targeting RIPK4.…”
Section: Discussionmentioning
confidence: 99%
“…there are a few of reports regarding the role of RIPK4 and potential mechanism in OC.Liu et al have reported that RIPK4 can act as a potential prognostic molecular marker for poor survival and promoted tumor metastasis in OC (S Liu et al, 2021)…”
mentioning
confidence: 99%